A predictive TRNSYS model for long-term operation of a hybrid ground source heat pump system with innovative horizontal buried pipe type. (May 2020) - Hou, Gaoyang; Taherian, Hessam; Li, Longjun
Abstract: This study presents an integrated hybrid ground source heat pump (HGSHP) predictive model assisted by liquid dry cooler (LDC). Combining with a new computational component imported to Transient System Simulation Tool (TRNSYS), the long-term simulation results proves that the HGSHP has better performance comparing to conventional ground source heat pump. In Birmingham, USA area, surrounding soil thermal storage is decreasing over time for both hybrid and conventional systems. After 10 years of simulation, the minimum temperature in the target zone is 12.53 °C for the HGHSP, which is 0.63 °C higher than the value of the conventional GSHP. The coefficient of performance (COP) for the hybrid system could stay at 3.33, which is also better than 3.23 for the conventional system. All the collected data shows that HGSHP integrated with liquid dry cooler plays an important role to maintain the soil thermal storage as well as promoting the overall system performance. Highlights: An Innovative HGSHP with horizontal ground loop and liquid dry cooler is proposed. A TRNSYS type to analyze soil thermal variation of horizontal loops is implemented. Long-term soil thermal balance of hybrid and conventional systems is compared. The solution to soil thermal capacity degradation is introduced.